Illness Seeking Behavior and Self-Medication Practice Among Medical Students: A Cross Sectional Study - Musa, Nighat; Mehmood, Yasir; Khan, Asghar (Journal of Gandhara Medical and Dental Science, 2019)
OBJECTIVES: To determine the illness seeking behavior and self-medication among students of private medical college in Peshawar. METHODOLOGY: This study was a cross sectional descriptive study. It was conducted from September till December 2018. Study setting was a private medical college of Peshawar. A total of 250 students were recruited after taking well informed consent. Sampling technique was stratified sampling, from every academic year proportional number of students was selected for the study. Pilot study to check feasibility of questionnaire was done on 10% sample size. Data was collected from students by face-to-face interviews. Data was entered and analyzed in SPSS version 21. RESULTS: The study data regarding illness-seeking behaviors among medical students showed that 162 (64.8%) out of 250 practiced self-medication. The common illness was fever, headache and sore throat. Students used pain-killers and antibiotics without getting consultation. CONCLUSION: Self-medication is common among medical students of all five professional years in medical college of Gandhara University Peshawar. Regarding illness seeking behaviors most of the students preferred self-medication as most of the time medicines are available without prescription in the medical stores. However, still some percentage of students prefers to consult doctors or pharmacist before taking any medicine for their illness. KEYWORDS: Illness, Behavior, Self-Medication, Medical Students, Headache